MEASURING ONLINE LEARNING READINESS DURING CORONA VIRUS PANDEMIC: AN EVALUATIVE SURVEY ON HISTORY TEACHERS AND STUDENTS - Atqo Akmal; Asyrul Fikri; Tien Rahmawati; Zulfa Hendri; Noviyana Sari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Corona virus pandemic has rapidly changed the way of life as well as the way of learning system in entire world. The need for information and communication technology (ICT) competencies and improved digital infrastructure are the main requirement to conduct the distance learning or online learning. In addition, both teachers and students must be adapted with this “abnormal” condition since the online learning has been officially applied by Indonesian government during March until end of 2020. However, a quick change to online learning has left students and teachers with insufficient time to prepare. This study focused on the readiness of teachers and students to conduct online learning. The readiness aspects considered in this study were the digital competence of users and digital infrastructure readiness to support the technical issue of online learning. The design of this study was evaluative survey and the data were collected equally by using online survey platform from three hundreds high school students and thirty history teachers. To maintain the equalization of the data, the respondent was divided into two clusters, based on the rural region and urban region. This study found that both students and teachers were mainly not well prepared and fully ready to conduct online learning due to technical problems such as stability of internet access, the internet network availability, and financial issues. Meanwhile, the digital competence aspect was not the major problem for both teachers and students because the majority of respondents (above 80%) declared that they had no trouble in using the device or running the online learning platform. Consequently, in a long-term effect, the unbalanced preparation of online learning could be resulted in digital divide which rose the inequality of the education quality among the learners.